Biocomposites of poly(lactic acid) and lactic acid oligomer‐grafted bacterial cellulose: It's preparation and characterization. Issue 35 (2nd May 2019) - Patwa, Rahul; Saha, Nabanita; Sáha, Petr; Katiyar, Vimal
ABSTRACT: This work demonstrates the synthesis of lactic acid oligomer‐grafted‐untreated bacterial cellulose (OLLA‐ g ‐BC) by in situ condensation polymerization which increased compatibilization between hydrophobic poly(lactic acid) (PLA) and hydrophilic BC, thus enhancing various properties of PLA‐based bionanocomposites, indispensable for stringent food‐packaging applications. During the synthesis of OLLA‐ g ‐BC, hydrophilic BC is converted into hydrophobic due to structural grafting of OLLA chains with BC molecules. Subsequently, bionanocomposites films are fabricated using solution casting technique and characterized for structural, thermal, mechanical, optical, and gas‐barrier properties. Morphological images showed uniform dispersion of BC nanospheres in the PLA matrix, which shows strong filler–matrix interaction. The degradation temperatures for bionanocomposites films were above PLA processing temperature indicating that bionanocomposite processing can be industrially viable. Bionanocomposites films displayed decrease in glass transition ( T g ) and ~20% improvement in elongation with 10 wt % fillers indicating towards plasticization of PLA. PLA/OLLA‐ g ‐BC films showed a slight reduction in optical transparency but had excellent UV‐blocking characteristics. Moreover, dispersed BC act as blocking agents within PLA matrix, reducing the diffusion through the bionanocomposite films which showed ~40% improvement in water‐vapor barrier by 5 wt % filler addition, which is significant. The reduced T g, improved elongation combined with improved hydrophobicity and water‐vapor barrier make them suitable candidate for flexible food‐packaging applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47903. Abstract :